Identification and management of infections caused by Giardia sp., Trichuris sp. and Demodex sp. in captive Brazilian porcupines (Coendou prehensilis) - Gastón Moré; Peggy Rüegg-van den Broek; Olivier J. Glardon; Diana S. Gliga; Caroline F. Frey; Walter Basso (International Journal for Parasitology: Parasites and Wildlife)
The Brazilian porcupine (Coendou prehensilis, Rodentia, Erethizontidae) is an arboreal South American nocturnal rodent. Switzerland is home to one of the largest captive colonies in Europe. In June 2022, most of the animals in this colony showed severe diarrhoea, and Giardia sp. cysts were detected. All the animals were treated with metronidazole (75 mg/animal/day orally) for five days, repeating after two weeks. The diarrhoea continued, sometimes containing blood, and further analyses revealed Giardia sp. cysts and Trichuris sp. eggs with a particular undulating eggshell in pooled samples. The soil layer of some enclosures was removed to thoroughly clean and disinfect the underlying concrete floor. The animals were treated with fenbendazole (50 mg/kg/day orally) for 5 days repeating after three days. Giardia sp. cysts were not further detected. However, Trichuris sp. eggs were detected in branch bark samples and in six animals 2–3 months after treatment. The treatment with fenbendazole was repeated and no further Trichuris sp. eggs were detected. A 18S rRNA fragment consensus sequence showed 98.58% identity with Trichuris fossor. The Trichuris sp. in C. prehensilis may represent a new species, specific for arboreal porcupines. Demodex mites were observed in faecal flotations and thereafter in skin scrapings from five animals (four of them being family-related). A 16S consensus sequence showed 86.4% identity with other Demodex species. The animals were initially treated with moxidectin (0.4 and 0.8 mg/kg orally) and afterwards with sarolaner (10 mg/animal) but the treatments were not completely effective since in control scrapings, two animals evidenced few non-motile mites. An individual susceptibility and poor immunological control of the infection is suggested. Treatment with fenbendazole was effective against Giardia sp. and Trichuris sp. infections; however, reinfections may occur if the enclosures and tree branches are not deep cleaned and disinfected or replaced.